2018
DOI: 10.29121/granthaalayah.v6.i7.2018.1302
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis and Design of Guided Inquiry E-Worksheet Based to Develop High Order Thinking Skills

Abstract: The aims of this research were to analyze the needs and to design electronic worksheet to develop High Order Thinking Skills (HOTS) in static fluid material at Islamic High School Ar Raihan and SMAN 6 Bandar Lampung. The research method used in this study was two steps of Research and Development (R&D) with mixed methods. Step 1: analyze the needs by doing: (a) front end analysis including analyze the needs of teachers and students, and (b) learner analysis which focused on students’ HOTS with pre experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Stages of the lesson study included plans, do, and see [19]. Recently, learning models based on lesson study have been successfully reported to improve learning outcomes of students [20] [21] [22], to develop pre-service teachers' capacity in teaching science [23] [24], to increase critical thinking skills [25], to enhance mathematics teachers' quality [26], to improve chemistry teacher competency [27] and to build students' character [28].…”
Section: Introductionmentioning
confidence: 99%
“…Stages of the lesson study included plans, do, and see [19]. Recently, learning models based on lesson study have been successfully reported to improve learning outcomes of students [20] [21] [22], to develop pre-service teachers' capacity in teaching science [23] [24], to increase critical thinking skills [25], to enhance mathematics teachers' quality [26], to improve chemistry teacher competency [27] and to build students' character [28].…”
Section: Introductionmentioning
confidence: 99%
“…The process of distance learning or online learning is very need of information technology (Hanifah Salsabila et al, 2020). Teachers must have classroom management skills by utilizing information and communication technology (Riyadi et al, 2018). Because of this condition, the use of Electronic LKPD is very effectively used by students, especially during the Pademic.…”
Section: Discussionmentioning
confidence: 99%
“…Sehingga untuk mendukung model pembelajaran problem based learning guru membutuhkan model pembelajaran dan bahan ajar yang dapat meningkatkan kemampuan berfikir secara kreatif (Umriani and Suparman, 2019). Begitu pula dengan hasil penelitian Bli Riyadi yang menyatakan bahwa hasil pengembangan Elektronik LKPD berbasis inkuiri efektif dalam meningkatkan kemampuan berpikir HOTS siswa (Riyadi, Ertikanto and Suyatna, 2018).…”
Section: Gambar 5 Gambar Tampilan Isi E-lkpdunclassified